Two cases of achalasia (mega-oesophagus), secondary to encephalitis - İnce, Lâtife and Özbay, Neclâ and Oto, Nuri (The Turkish Journal of Pediatrics, 1971)
In the light of our two cases and the review of the medical literature in the pathogenesis of achalasia, a lesion of the brainstem or of the dorsal nucleus of the vagus and its preganglionic fiber may be a cause of motor disturbance of the entire oesophagus, as much as a lesion of the Auerbach’s plexus itself. Therefore we believe that our two cases of achalasia secondary to encephalitis confirm this observation.